The Effect of Green Marketing, Brand Image, and Atmosphere Store On Purchasing Decisions In Arei Adventure Store Surabaya 3 - Aqsony, Yanuar Bachrul; Soebandhi, Santirianingrum; Wulandari, Ani (Yayasan Ahmar Cendekia Indonesia, 2020)
Purchasing decisions are one thing that is very influential in a product. Many factors influence purchasing decisions, including green marketing activities, brand image, and store atmosphere. The purpose of this study was to determine how the influence of green marketing, brand image, and store atmosphere both simultaneously and partially on purchasing decisions at Arei Adventure Store Surabaya 3. Data collection used was a questionnaire. The research method employed a random sample of 101 people. The analytical method mobilized was SPSS 24. The results of this study indicated that the independent variables simultaneously influence the dependent variable. This was evidenced from the significance value of 0,000 or less than 0.05 and F count = 27.791 while the F value was obtained at 2.70. Thus F count 27.791> F table 2.70. However, partially the green marketing variable was not significant to the purchase decision because the test results showed the value of t count = 1.425 0.05.